2019
DOI: 10.1177/1940082919853764
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Wind Events Influence Seed Rain and Seedling Dynamics of Guam’s Serianthes nelsonii Merr

Abstract: The seasonal aspects of Guam's Serianthes nelsonii seed rain quantity, new seedling emergence, and lifespan of newly emerged seedlings were determined by direct observations. Two high wind events in January and September 2013 generated 63% of the annual number of new seeds collected in litterfall. A defoliating tropical cyclone in May 2015 generated an abrupt increase in seedling emergence with 17% of the annual new seedling count emerging during the 4-week period after the tropical cyclone. Of the annual coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This study revealed for the first time that regeneration was substantial, that seedling mortality was rapid, and that the major limitation to the natural expansion of the plant population was a failure of seedlings to recruit into the sapling stage. These methods were repeated using weekly visits to the tree from October 2014 until October 2015 [22]. Of the 243 seedlings that emerged during the 12-month period, 30% died in less than two weeks, corroborating the results of the first study [21].…”
Section: In Situ Regeneration Not a Limitationsupporting
confidence: 60%
“…This study revealed for the first time that regeneration was substantial, that seedling mortality was rapid, and that the major limitation to the natural expansion of the plant population was a failure of seedlings to recruit into the sapling stage. These methods were repeated using weekly visits to the tree from October 2014 until October 2015 [22]. Of the 243 seedlings that emerged during the 12-month period, 30% died in less than two weeks, corroborating the results of the first study [21].…”
Section: In Situ Regeneration Not a Limitationsupporting
confidence: 60%
“…For managed in situ populations, there is no reason for conservationists to waste seeds by allowing natural seed rain and germination beneath the source tree’s canopy. Years of research have revealed that these seedlings exhibit 100% mortality [ 28 , 29 ]. Using pruning to thin the canopy to determine if limited light is causal of the in situ seedling mortality is not possible if the seedlings are growing beneath the canopy of an endangered tree.…”
Section: Discussionmentioning
confidence: 99%
“…The species is characteristic of several tree species from the Mariana Islands in that the declining populations are comprised of large adults with few saplings and juveniles. Recent conservation research has revealed that recruitment is substantial, and the regeneration failures are due to rapid seedling mortality [ 28 , 29 ]. No contemporary seed vector is known, so 100% of observed seedlings emerge under the parent trees where incident light is severely limited.…”
Section: Introductionmentioning
confidence: 99%
“…To date, not a single tree has been nurtured to maturity and little progress has been made toward reaching these goals. In situ regeneration and horticultural propagation are not limitations to species recovery [18][19][20]. In contrast, in situ recruitment to the sapling stage and successful establishment of nursery stock after out-planting from a nursery are acute limitations.…”
Section: Final Thoughtsmentioning
confidence: 99%
“…The species has been listed as Endangered under the United States Endangered Species Act (ESA) since 1987 [16], and a formal recovery plan has been in place since 1994 [17]. A recent publication illuminated the negative consequences to conservation of this species that resulted from the historical use of extemporary short-term contract approaches rather than an integrated, sustainable conservation approach [18].…”
mentioning
confidence: 99%